2013
DOI: 10.1111/ajop.12029
|View full text |Cite
|
Sign up to set email alerts
|

School‐ and community‐based associations to hypermasculine attitudes in African American adolescent males.

Abstract: This study examined the role of hypermasculinity as a form of reactive coping among urban African American adolescent males (ages 12-17) and assessed the extent to which hypermasculinity is influenced by youth appraisals of how adults in their school and community perceive them. Two research questions were addressed: (a) Do adolescent males who report negative community and school experiences use hypermasculine attitudes as a coping response? (b) Do the effects of perceived negative school and community experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…This is consistent with previous research that links challenging community environments to the development of forms of masculinity that celebrate dominance, aggression, and sexual conquest (Cunningham et al, 2013). These masculinity attitudes have been hypothesized to have adaptive value in some circumstances, as young men cope with the dangers inherent in disadvantaged communities.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research that links challenging community environments to the development of forms of masculinity that celebrate dominance, aggression, and sexual conquest (Cunningham et al, 2013). These masculinity attitudes have been hypothesized to have adaptive value in some circumstances, as young men cope with the dangers inherent in disadvantaged communities.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also reveal the intersectional nature of dominant ideologies and boys' resistance and accommodation to them. The "boy code" and the "cool pose," for example, are gendered, raced, sexualized (i.e., heterosexual), and classed [Cunningham et al, 2013;Dumas & Nelson, 2016;Way & Rogers, 2014]. The "Black box" that Marcus describes in his identity narrative is explicitly racialized but also implicitly classed, gendered, and sexualized.…”
Section: Discussionmentioning
confidence: 99%
“…32-33) While developmental researchers have not considered the study of gender socialization, for example, as a study of accommodation to ideological structures, it is, in fact, the study of how boys and girls adopt dominant gender ideologies in their peer groups, identities, and school behaviors [e.g., Cvencek et al, 2011;Fabes et al, 2004;Liben, 2017;Tobin et al, 2010]. The study of boys, in addition, typically reveals how boys align with masculine norms [Chu, Porche, & Tolman, 2005;Cunningham, Swanson, & Hayes, 2013;Kimmel, 2008;Pleck, Sonenstein, & Ku, 1993;Majors & Billson, 1992;Tolman, Davis, & Bowman, 2015]. Developmental studies have also focused on accommodation to racist ideologies and revealed how children "learn" or accommodate to such ideologies in their racial attitudes and stereotypes [e.g., Slaughter-DeFoe, 2012].…”
Section: Accommodation and Resistance To Cultural Ideologiesmentioning
confidence: 99%
See 2 more Smart Citations